Microdialysis techniques and microdialysis-based patient-near diagnostics - O'Connell, Mark Thomas; Krejci, Jan (Analytical and bioanalytical chemistry, 2022)
This article will debate the usefulness of POCT measurements and the contribution microdialysis can make to generating valuable information. A particular theme will be the rarely considered difference between ex vivo sampling, which typically generates only a static measure of concentration, and in vivo measurements that are subject to dynamic changes due to mass transfer. Those dynamic changes provide information about the patients' physiological state.
Keywords: Point-of-care testing; mikrodialýza; Sensors; Humans; Microdialysis; lidé